2018
DOI: 10.1007/s10290-018-0312-x
|View full text |Cite
|
Sign up to set email alerts
|

Export characteristics and output volatility: comparative firm-level evidence for CEE countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Others have instead focused on the impact of international trade on volatility. In particular, some of the latter studies have found that exporters sales growth rate volatility is on average greater than non-exporters (Ćede et al, 2018;Vannoorenberghe, 2012). Furthermore the reallocation of market shares between foreign and domestic incumbents impacts the odds to grow or to shrink also at higher levels of aggregation (i.e.…”
Section: Empirical and Theoretical Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have instead focused on the impact of international trade on volatility. In particular, some of the latter studies have found that exporters sales growth rate volatility is on average greater than non-exporters (Ćede et al, 2018;Vannoorenberghe, 2012). Furthermore the reallocation of market shares between foreign and domestic incumbents impacts the odds to grow or to shrink also at higher levels of aggregation (i.e.…”
Section: Empirical and Theoretical Backgroundsmentioning
confidence: 99%
“…Finally, the increasing importance of international competition, fostered by the fall of trade barriers in the last decades, has increased the awareness about the signi cant impact of trade ows on industry and rm dynamics. In that respect, recent studies have found that market concentration (di Giovanni et al, 2011) and volatility (di Giovanni and Levchenko, 2009, 2012Vannoorenberghe, 2012;Ćede et al, 2018;di Giovanni et al, 2019) are positively a ected by trade openness.…”
Section: Introductionmentioning
confidence: 99%
“…Rolling window of 7-year intervals, that is, midpoints of these periods, are presented. For example; 1981Q3 presents 1978Q1-1984Q4 period researchers (Buch, Doepke, & Stahn, 2008;Čede, Chiriacescu, Harasztosi, Lalinsky, & Meriküll, 2016;Owyang et al, 2008).…”
Section: And Structural Break Smentioning
confidence: 99%
“…Let y be the variable of interest (i.e., de‐trended employment), so that volatility is basically obtained by calculating standard deviation of y for the period. It has been used widely by many researchers (Buch, Doepke, & Stahn, ; Čede, Chiriacescu, Harasztosi, Lalinsky, & Meriküll, ; Owyang et al, ).…”
Section: National Employment Volatility: Analysis and Structural Breaksmentioning
confidence: 99%
“…Specialisation constitutes the foundation for economic concentration which in turn implies export concentration. Where openness is characterized by greater export concentration, this may engender volatility in output growth (Čede, et al, 2016;Haddad, et al (2013). However, where exports are diversified (especially vertically and geographically), trade openness may engender stability in output growth, as diversification provides the economy some buffer against the effect of exogenous shocks (Busch, 2011;Ali, 2016).…”
Section: Introductionmentioning
confidence: 99%